ANALISIS KESEDIAAN MASYARAKAT MENERIMA PEMBAYARAN JASA LINGKUNGAN DALAM PENGELOLAAN AIR MINUM DI DAS CISADANE HULU - Sutopo, M.Fauzi (Jurnal Hidrosfir Indonesia, 2010)
Ecocentrisme paradigm in development are intended to ensure the sustainability of water resources in the future for future generations. The research methodology was conducted with the model approach the public's willingness to accept (receive) payment for environmental services (YWTA). The results in Willingness to Accept Model in Drinking Water Management in the Upstream Watershed Cisadane illustrates that the existence of community support during the response level of society's willingness to accept or receive payment for environmental services (YWTA) because it will affect the increased revenue (sig. 0037). Variable in income (YWTA) significant at 95% confidence level. Policy implications of this research that the community (upstream) is willingness to accept (WTA) for environmental services with averaging Rp 1.589,29 per m3 as payment or reward for environmental services to society (upstream), so the Government (Local)PES has a potential revenue to fund conservation of Rp 110,46 billion per years, but in current conditions the government only accepts Rp20.57 billion per year, so that only reached 18,62%.